Pengaruh Faktor Motivasi Kerja Ditinjau dari Aspek Finansial, Lingkungan Kerja dan Penghargaan terhadap Kinerja Pegawai Biro Kepegawaian Sekretariat Daerah Provinsi Kalimantan Selatan - Anwar, Mahfuzil (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2017)
This study aims to obtain empirical evidence about the influence of motivational factors through the financial aspects, Work Environment and employee performance appraisals, the Civil Service Bureau of the Regional Secretariat of South Kalimantan Province. The hypothesis put forward is a hypothesis I, Simultaneously Finance, Working Environment Award and affect the performance of employees in the Civil Service Bureau of the Regional Secretariat of South Kalimantan Province. Hypothesis II partial financial aspect is more dominant influence on the performance of employees in the Civil Service Bureau of the Regional Secretariat of South Kalimantan Province. Through a questionnaire submitted to the respondent on the financial aspects with 20 items of questions, aspects of the work environment with 11 items of questions, and aspects of the awards with 9 items of questions, with three alternative answers a, b and c with a score of 3.2, and 1. The questionnaire performance with 16 items of questions and respondents as many as 102 people. The results showed that the hypothesis I stating together the financial aspects, work environment and rewards affect the performance of employees at the Civil Service Bureau of the Regional Secretariat of South Kalimantan Province, is acceptable. Hypothesis II stating financial has more dominant influence on the performance of employees in the Civil Service Bureau of the Regional Secretariat of South Kalimantan Provinceconvicted.Keywords: Finance, working environment, and Performance Award